2020
DOI: 10.1126/science.aaw4325
|View full text |Cite
|
Sign up to set email alerts
|

Memory engrams: Recalling the past and imagining the future

Abstract: In 1904, Richard Semon introduced the term “engram” to describe the neural substrate for storing memories. An experience, Semon proposed, activates a subset of cells that undergo off-line, persistent chemical and/or physical changes to become an engram. Subsequent reactivation of this engram induces memory retrieval. Although Semon’s contributions were largely ignored in his lifetime, new technologies that allow researchers to image and manipulate the brain at the level of individual neurons has reinvigorated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
678
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 740 publications
(711 citation statements)
references
References 241 publications
(195 reference statements)
23
678
8
2
Order By: Relevance
“…Long-term potentiation (LTP) of synaptic function is considered the major process underlying learning and memory 1 where it is involved in synaptic engram formation 2,3 , yet the underlying cellular mechanisms remain incompletely understood. The best-characterized form of LTP occurs at the Schaffer collateral-commissural pathway (SCCP) in the hippocampus, where it is triggered by synaptic activation of NMDA (N-methyl-D-aspartate) receptors 4 and is expressed as a persistent increase in AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid) receptor-mediated synaptic transmission 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Long-term potentiation (LTP) of synaptic function is considered the major process underlying learning and memory 1 where it is involved in synaptic engram formation 2,3 , yet the underlying cellular mechanisms remain incompletely understood. The best-characterized form of LTP occurs at the Schaffer collateral-commissural pathway (SCCP) in the hippocampus, where it is triggered by synaptic activation of NMDA (N-methyl-D-aspartate) receptors 4 and is expressed as a persistent increase in AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid) receptor-mediated synaptic transmission 5 .…”
Section: Introductionmentioning
confidence: 99%
“…To synthesize a productive associative memory that elicits an adaptive response upon future encounter with the CS, both the CS and the US must be encoded in the neural system. Moreover, their encoding needs to be logically integrated such that the behavioral response will match the expected valence that the CS predicts (Josselyn and Tonegawa, 2020) .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, mammalian brains are thought to encode associative memories in a decentralized fashion where interconnected areas, distributed throughout the entire brain, link up to encode memory traces. For example, associative fear memories are thought to be distributed among the amygdala that encodes the valence , the hippocampus which encodes the context, and the cortical neurons which provide the specific sensory information (Josselyn and Tonegawa, 2020) . Furthermore, sensory neurons proved to play intriguing roles in formation of associative memories.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that hippocampal neurons also encode a wide range of non-spatial information that enables cognitive functions beyond spatial navigation 36 . However, we still lack a clear understanding of how cognitive maps emerge during learning 2,7–9 . By studying subjects performing foraging or reinforcement learning tasks, we limited ourselves in observing neural activities associated with overt behavioral changes, whereas cognitive maps can be acquired and stored implicitly.…”
mentioning
confidence: 99%
“…We provided a mechanism showing how a cognitive map can be built via latent learning and stored as a neural manifold. Although we only investigated simple 2D spatial exploration experiences, with our framework, non-spatial information such as sensory cues, reward, behavioral states, and even the concept of time can all be stored in same the manifold, likely in the other dimensions, providing a holistic, schema like representation of the animal’s experience 2,7–9,33 . Our work also showcased the often- neglected WS cells in the HPC, demonstrating the importance of understanding heterogeneity in the HPC neurons 34,35 .…”
mentioning
confidence: 99%